Four Models of Protecting Citizenship and Social Rights in Europe: Conclusions to the Special Issue 'Rethinking the European Social Market Economy'. (28th November 2018) - Claassen, Rutger; Gerbrandy, Anna; Princen, Sebastiaan; Segers, Mathieu
Abstract: This article offers a synthesis of and conclusion to the contributions included in the Special Issue 'Rethinking the European Social Market Economy'. Based on different understandings of citizenship in the European Union and the roles of the EU and its member states in providing social protection arrangements, it develops a typology of four models of the EU's role in social protection. It then discusses the contributions to this Special Issue in light of this typology and draws a number of overarching conclusions.